PERANCANGAN EDUWISATA PECINTA ALAM DI DESA GEKBRONG, CIANJUR DENGAN KONSEP ARSITEKTUR HIJAU - Ori Okta Vianda; Anggraeni Dyah Sulistiowati; Sri Kurniasih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2022)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, and skills needed by society. Educational tourism itself is a type of special interest tourism that is categorized according to certain motivations which are usually related to time, hobbies and the pursuit of leisure, where there is a combination of recreation and education. So therefore, with the design of the nature activist edutourism design, it is hoped that it can accommodate and facilitate nature activist and facilities that support nature activities, Provide educational facilities as a contribution to environmentally conscious nature activist, Contribute the percentage of public green open space in Cianjur City, and enrich education-based tourist destinations in the city of Cianjur. Cianjur City. However, it can become an education-based tourist destination that focuses on training in human resource development and introduces the importance of being environmentally aware.